Evolution of Free Amino Acids, Histamine and Volatile Compounds in the Italian Anchovies (Engraulis encrasicolus L.) Sauce at Different Ripening Times - Onofrio Corona; Luciano Cinquanta; Caterina Li Citra; Francesca Mazza; Vincenzo Ferrantelli; Gaetano Cammilleri; Emanuele Marconi; Francesca Cuomo; Maria Cristina Messia (Foods, 2022)
In this study, the evolution of the safety, nutritional, and volatile profile of a traditional Italian anchovy sauce with protected designation of origin (PDO), called “colatura di alici di Cetara”, is investigated after 12, 24, and 48 months of aging in wooden barrels. Some physicochemical parameters, free amino acids, volatile compounds, and histamine contents were evaluated during the aging of the samples. Glutamate, which together with aspartate is responsible for the umami taste, was the predominant free amino acid in the tested fish sauce, with a significant increase during the 48 months of maturation. The total amino acid content of the anchovy sauce increased from 24 to 48 months of aging. The histamine content decreased significantly from 12 to 48 months of ripening. This point is particularly interesting for the sauce safety and confirms the importance of the maturation time of at least 9 months reported in the disciplinary of production. A total of 44 volatile compounds were found in the anchovy sauce samples, of which the largest class was acids, mainly isovaleric acid. The results show that prolonged maturation improves the safety, nutritional, and volatile components of the seasoning “colatura di alici”.